Arms and the woman : classical tradition and women writers in the Venetian Renaissance - D'Alessandro Behr, Francesca (Classical memories/modern identities., 2018)
"Focuses on classical reception in the works of female authors active in Venice during the Early Modern Age. Explores the work of Moderata Fonte and Lucrezia Marinella and demonstrates how they used knowledge of texts by Virgil, Ovid, and Aristotle to promote gender-based egalitarianism"--